1993
DOI: 10.1016/0014-5793(93)80738-g
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic analysis of myosin heavy chain isoform patterns in extraocular muscles of the rat

Abstract: Six oculorotatory muscles and the levator palpebrae muscle of the rat were analysed by SDS-PAGE for their myosin heavy chain (MHC) isoform patterns. Oculorotatory muscles display a marked predominance of fast MHC isoforms. They contain, in addition to the slow (MHCI) and fast (MHCIIb, MHCIId, MHCIIa) skeletal MHCs, the neonatal MHC, and the extraocular MHC,,. The levator palpebrae, generally assumed to be a member of the extraocular muscle group because of its innervation by the ocohnnotor nerve, does not cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Even though EOM contains a large number of slow muscle fibers, it is still considered one of the fastest muscles in the vertebrate body (15). One-dimensional electrophoresis previously showed that in EDL, a fast isoform (MYH4) accounted for ϳ45% of all MYH, whereas in EOM fast MYH (MYH4 and MYH13) accounts for 75% (13,18,38). Considering the higher amount of fast MYH in EOM, the elevated expression level of SLIM in EOM correlates well.…”
Section: Table II Proteomics Profile Of Extraocular Muscle Versus Extmentioning
confidence: 91%
See 1 more Smart Citation
“…Even though EOM contains a large number of slow muscle fibers, it is still considered one of the fastest muscles in the vertebrate body (15). One-dimensional electrophoresis previously showed that in EDL, a fast isoform (MYH4) accounted for ϳ45% of all MYH, whereas in EOM fast MYH (MYH4 and MYH13) accounts for 75% (13,18,38). Considering the higher amount of fast MYH in EOM, the elevated expression level of SLIM in EOM correlates well.…”
Section: Table II Proteomics Profile Of Extraocular Muscle Versus Extmentioning
confidence: 91%
“…Previous one-dimensional gel electrophoresis approaches failed to resolve all MYH present in EOM because of their close mass range (13,14), and most data concerning protein abundance were gained by immunohistochemistry (12).…”
Section: Table I Correlation With Microarray Datamentioning
confidence: 99%
“…2) as previously described (1). Because MyHC-IIa is the main MyHC isoform in type 2A fibers (9), and MyHC-IIa is a major constituent of extraocular muscles (13), which were involved in all affected family members, the MyHC-IIa was regarded a very strong candidate gene for the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, mutations in ␤ cardiac͞slow MyHC have been reported to affect slow, type 1, muscle fiber structure and function (5,6). (vi) External ophthalmoplegia is compatible with a pathogenic mutation affecting IIa MyHC because this is a major isoform of myosin in extraocular muscle (13). (vii) Targeted disruption of fast MyHC genes in mice causes myopathy with muscle weakness and disorganization of myofilaments (18), and point mutations in MyHC genes cause muscle dysfunction in Drosophila, Caenorhabditis elegans, and Dictyostelium (16).…”
Section: Discussionmentioning
confidence: 99%
“…MHCir displayed a lower mobility than MHC,,, (Fig. 2, lane 3), an isoform previously identified by SDS-PAGE in extraocular muscles of rabbit [21] and rat [22].…”
Section: Electrophoretic Analysesmentioning
confidence: 99%